Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1029/2006gl028037
|View full text |Cite
|
Sign up to set email alerts
|

SAM and regional rainfall in IPCC AR4 models: Can anthropogenic forcing account for southwest Western Australian winter rainfall reduction?

Abstract: Winter rainfall over southwest Western Australia (SWWA) has decreased by 20% since the late 1960s. Why has the reduction occurred in the Southern Hemisphere (SH) winter months but not in summer? To what extent is this reduction attributable to anthropogenic forcing and congruent with the Southern Annular Mode (SAM)? Using reanalysis data and the Intergovernmental Panel on Climate Change 4th Assessment Report (IPCC AR4) 20th century model experiments, we show that a SAM‐SWWA relationship exists in winter and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
143
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(150 citation statements)
references
References 24 publications
(36 reference statements)
7
143
0
Order By: Relevance
“…Several SAM indices are available; we use the index based on Marshall (2003) available from David Thompson's website. This SAM index is close to the index previously used in studies of SWWA precipitation by Cai and Cowan (2006).…”
Section: Datamentioning
confidence: 69%
See 2 more Smart Citations
“…Several SAM indices are available; we use the index based on Marshall (2003) available from David Thompson's website. This SAM index is close to the index previously used in studies of SWWA precipitation by Cai and Cowan (2006).…”
Section: Datamentioning
confidence: 69%
“…The results clearly show that the unique contributions of IOH pressure and longitude to the variability of SWWA winter precipitation exceed those of the SOI, IOD and SAM. Cai and Cowan (2006) have studied the relationship between SWWA JJA rainfall and the Southern Annular Mode during 1950-1999 by using a modification of the SAM data of Marshall (2003). They did not use the principal component of the EOF which is commonly considered as the SAM index, but instead considered the inter-annual change in the average sea-level pressure in the EOF pattern and found its correlation with SWWA rainfall to be −0.30 which is statistically significant at the 95 per cent confidence level.…”
Section: Winter Precipitation Over Southwest Western Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…The rainfall decrease in SWWA has been studied intensely in recent years (e.g. Smith et al, 2000;Cai and Watterson, 2002;IOCI, 2002;Pitman et al, 2004;Cai et al, 2005;Cai and Cowan, 2006;Hope et al, 2006;Meneghini et al, 2007;Feng et al, 2010aFeng et al, , 2010b, as has the increasing trend in NWA (Wardle and Smith, 2004;Rotstayn et al, 2006;Shi et al, 2008aShi et al, , 2008bTaschetto and England, 2008). In contrast, relatively little is known of the cause and mechanism of the decreased NEA rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis showed that the most recent decline in rainfall in the Southern Slopes is within the range of variability given by the reconstruction. The cool-season decline in the south is often associated with the intensification of the subtropical ridge (Timbal and Drosdowsky, 2012;Timbal et al, 2006), changes in large-scale atmospheric circulation such as the Indian Ocean (Ummenhofer et al, 2011), and the observed upward trend in SAM (Cai and Cowan, 2006). All of these processes are significantly linked to interannual rainfall variability in the south (Fig.…”
Section: Discussionmentioning
confidence: 99%